Globalization and International Accounting Research: an agenda for the future - Manassian, Armond (Review of Business Management, 2007)
The study of international accounting is increasing in importance because of its ramifications upon business practices world-wide. International accounting is inextricably linked to the globalization movement that is sweeping all economies. Indeed, the availability of accounting information constitutes an integral and indispensable input to the existence and acceleration of this movement. This paper provides a step toward the examination of such beliefs and their impact on international accounting through a historical investigation of the academic literature in this field as exemplified by two journals: Advances in International Accounting and the International Journal of Accounting Education and Research. The wider project involved a hermeneutic interpretation of documents in an attempt to analyze trends in international accounting research appearing in academic accounting journals from 1987 to 1996 through the lens of postcolonialism. However, due to space constraints this paper focuses on the predominance and the championing of the globalization theme in this literature and its impact on research. This section of the paper provides a description of the methods employed in selecting the journals, the relevant time period, the articles constituting the data set, and the procedure followed in constructing the qualitative themes. Key-words: International accounting. Globalization. Postcolonialism.